İş değerlendirmesi - Orhan, Babür Niyazi (Fen Bilimleri Enstitüsü, 1991)
Çalışma düzeninin saklanmasında karşılaşılan sorunlar çok çeşitli olmakla beraber ücret tayini ve idaresi bu sorunların en önemli, kısmını oluşturmaktadır. İşçinin geliri olan ücret aynı zamanda işletmenin maliyet gideridir. Taraflar sık sık karşı karşıya gelmekte ve çekişmeler olmaktadır. işçi kesimi ücretinin artmasını istemektedir. işveren kesimi içinse, ücretin artması maliyetleri arttırmaktadır. Çatışan çıkarların çevrelediği böyle bir ortamda, çalışma düzeninin uyumlu olarak işleyebilmesi için ortak dayanma noktalarının bulunması kaçınılmaz bir zorunluluk olmaktadır. işte bu noktada iş değerlendirmesi ortaya çıkmaktadır. iş değerlendirmesi, aralarındaki önem, güçlük, fark ve benzerliklerin dikkâte alınarak işlerin değerlendirilmesi işlerin güçlük derecelerinin ve çalışanların karşısına çıkan yükümlülüklerin somut olarak tesbit edilmesi ile ilgili faaliyetlerdir.Günümüzde iş değerlendirmesi uygulaması, özellikle gelişmiş sanayi toplumlarının üzerinde sürekli durdukları bir. konudur. Bu çalışmada öncelikle ücret, ücret sistemleri, ücretin işçi-işveren yönünden önemi üzerinde durulmuştur. Sonra, yapılan iş ile değeri arasında ilişki kurarak oluşabilecek Ücret adaletsizliklerine çözüm getiren bir yöntem olan iş değerlendirmesi vo yöntemleri incelenmiştir, îşletme içi ücretin oluşumu, çalışma düzenine etkiler i»işçi-işveren örgünlerinin konuya karşı tutumları vb. konulara değinilmiştir". Son olarak Türkiye'de ilk defa endüstri düzeyinde uygulaması yapılan Metal Sanayii İş Gruplandırma Sistemi ve.sonuçlarına değinilmiştir.

The Classification Method; This method is widely used for salaried jobs, inc luding those in goverraent and service occupations. It is also used for manual jobs in some industries in which the same worker is called upon to perform a variety of more or less standardised jobs for which standart rates of remune ration can be fixed. The Factor Comparison Method; This method, which is less refined than point ra ting systems, is rather complicated in practice. For this and also for some other reasons it is not widely used. This method involves the ranking of different jobs in respect of certain factors. The Point Method; - To select and define the factors that will be used in evaluating the jobs. - The determine the number of degrees to be distin guished under each factor, and to describe them. - To assign point values to each degree of each factor. The analytical methods that use quantative values is more detailed for examination and description of the jobs is assessed in terms of permitting them to be evalua ted according to the grade or factor descriptions establis hed for the purpose. Finaly the job evaluation, which is a method that brings solution to the possible injustices of wage by estab lishing a relationship between the work its, and its methods, is examined. XVII - They will also try to get better job by working >. -': hard and getting much experience as soon as pos sible. - They will know their positions in the future for wage structure relating with their skill based on experience at work. - The workers will be productive and qualified at the work, so they will like their job very much. - The workers will feel better at the work about their equal payments in similar jobs. - They will try to' gain more experience at work to develope themselves in the industry. - The wage structure will be stable for all industries, For using the job evaluation, there are mainly two groups methods, non-analytical (non quantative) and analyti cal "(quantative) methods, such as; -:;:The ranking. ;method, - The Classification method, (are non quantatives) ; - The factor comparison method, - The point method. (are -quantatives.) » As the simplest job evaluation method, the ranking method and grade method are non-analytical methods that use non-quantatives values do define either grades in wich jobs will be placed or factors in terms of which they will be evaluated. The ranking method? This method is the simplest of all job evaluation methods. Moreover it entails placing the jobs in order of the demands they are considered. These operations are quite simple in the case of a small plant with only a few jobs, but may prove unsatisfactory in a larger plant with a con siderable number of jobs, some of which may be quite complex. XVI The Classification Method; This method is widely used for salaried jobs, inc luding those in goverraent and service occupations. It is also used for manual jobs in some industries in which the same worker is called upon to perform a variety of more or less standardised jobs for which standart rates of remune ration can be fixed. The Factor Comparison Method; This method, which is less refined than point ra ting systems, is rather complicated in practice. For this and also for some other reasons it is not widely used. This method involves the ranking of different jobs in respect of certain factors. The Point Method; - To select and define the factors that will be used in evaluating the jobs. - The determine the number of degrees to be distin guished under each factor, and to describe them. - To assign point values to each degree of each factor. The analytical methods that use quantative values is more detailed for examination and description of the jobs is assessed in terms of permitting them to be evalua ted according to the grade or factor descriptions establis hed for the purpose. Finaly the job evaluation, which is a method that brings solution to the possible injustices of wage by estab lishing a relationship between the work its, and its methods, is examined. XVII - They will also try to get better job by working >. -': hard and getting much experience as soon as pos sible. - They will know their positions in the future for wage structure relating with their skill based on experience at work. - The workers will be productive and qualified at the work, so they will like their job very much. - The workers will feel better at the work about their equal payments in similar jobs. - They will try to' gain more experience at work to develope themselves in the industry. - The wage structure will be stable for all industries, For using the job evaluation, there are mainly two groups methods, non-analytical (non quantative) and analyti cal "(quantative) methods, such as; -:;:The ranking. ;method, - The Classification method, (are non quantatives) ; - The factor comparison method, - The point method. (are -quantatives.) » As the simplest job evaluation method, the ranking method and grade method are non-analytical methods that use non-quantatives values do define either grades in wich jobs will be placed or factors in terms of which they will be evaluated. The ranking method? This method is the simplest of all job evaluation methods. Moreover it entails placing the jobs in order of the demands they are considered. These operations are quite simple in the case of a small plant with only a few jobs, but may prove unsatisfactory in a larger plant with a con siderable number of jobs, some of which may be quite complex. XVI The Classification Method; This method is widely used for salaried jobs, inc luding those in goverraent and service occupations. It is also used for manual jobs in some industries in which the same worker is called upon to perform a variety of more or less standardised jobs for which standart rates of remune ration can be fixed. The Factor Comparison Method; This method, which is less refined than point ra ting systems, is rather complicated in practice. For this and also for some other reasons it is not widely used. This method involves the ranking of different jobs in respect of certain factors. The Point Method; - To select and define the factors that will be used in evaluating the jobs. - The determine the number of degrees to be distin guished under each factor, and to describe them. - To assign point values to each degree of each factor. The analytical methods that use quantative values is more detailed for examination and description of the jobs is assessed in terms of permitting them to be evalua ted according to the grade or factor descriptions establis hed for the purpose. Finaly the job evaluation, which is a method that brings solution to the possible injustices of wage by estab lishing a relationship between the work its, and its methods, is examined.
Job evaluation
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1991
Keywords: İşletme; Metal endüstrisi; Ücret; Ücret sistemleri; İş değerlemesi; İşletmeler; Business Administration; Metal industry; Wage; Wage systems; Job evaluation; Businesses